The Correlation between Self-Control and Conformity in Students Involved in Clubbing Activities in Yogyakarta Club - Giacinta, Elisabeth; Yuwono, Emmanuel Satyo (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
This study aims to determine the relationship between self-control and conformity in students involved in clubbing activities in Yogyakarta clubs. This study uses a quantitative approach with a non-parametric correlation method. The measuring instrument used is the Brief Self Control Scale (BSCS) to measure self-control, and a conformity scale compiled based on the normative and informative influence aspects of Myers (2012). The results of the analysis showed a significant negative relationship between self-control and conformity. The higher the student's self-control, the lower the level of conformity in clubbing activities. The linearity test also confirmed that the relationship between the two variables is linear. This finding confirms the important role of self-control in responding to group pressure in social contexts such as clubbing.